The correlation between serum Cyclophilin A level and severity, prognosis of craniocerebral injury - Li, Peng-Fei; Zhang, Jing-Chen; He, Xu-Jian; Niu, Jian-Hua; Wu, Wei-Fang; Li, Tong (Frontiers in Neurology, 2022)
Background To investigate the value of serum Cyclophilin A(Cyp A) in evaluating the prognosis of patients with different severity of craniocerebral injury. Methods The clinical data of patients with craniocerebral injury treated in the Department of Emergency from July 2014 to August 2017 were collected. The patients were divided into survival group and death group with 28-day prognosis and were divided into mild (13-15) group, moderate (9-12) group, and severe (3-8) group with Glasgow Coma Scale (GCS) score. Clinical parameters such as Cyp A and mortality in groups and the relationship between Cyp A and GCS score were compared and its predictive value for prognosis was analyzed with a SPSS 22.0 software. Results In a single-center prospective study, 503 patients were enrolled, including 365 males and 138 females; serum Cyp A in the survival group was significantly smaller than the death group18.7(10.1,51.5)ng/mL vs. 149.8(79.5，194.4)ng/mL, P 0.005. There were significant differences in mortality and Cyp A levels between patients with different severity of craniocerebral injury. (P < 0.001). Serum Cyp A levels were negatively correlated with GCS scores in all patients with craniocerebral injury, mild, moderate, or severe craniocerebral injury (r = -0.844, r = -0.256, r = -0.540, r = -0.531, P 0.001). Predictive value of Serum Cyp A level for all patients with craniocerebral injury, mild, moderate, and severe craniocerebral injury is 0.890, 0.789, 0.806, and 0.833, respectively. Conclusion Serum Cyp A has a certain predictive value for the prognosis of patients with different severity of craniocerebral injury. Among them, patients with severe craniocerebral injury have the highest predictive value and mild craniocerebral injury patients have the least.